Declarations of dependence: labour, personhood, and welfare in southern Africa. (1st May 2013) - Ferguson, James
<x xml:space="preserve">Abstract</x> Dependence on others has often figured, in liberal thought, as the opposite of freedom. But the political anthropology of southern Africa has long recognized relations of social dependence as the very foundation of polities and persons alike. Reflecting on a long regional history of dependence 'as a mode of action' allows a new perspective on certain contemporary practices that appear to what we may call 'the emancipatory liberal mind' simply as lamentable manifestations of a reactionary and retrograde yearning for paternalism and inequality. Instead, this article argues that such practices are an entirely contemporary response to the historically novel emergence of a social world where people, long understood (under both pre‐capitalist and early capitalist social systems) as scarce and valuable, have instead become seen as lacking value, and in surplus. Implications are drawn for contemporary politics and policy, in a world where both labour and forms of social membership based upon it are of diminishing value, and where social assistance and the various cash transfers associated with it are of increasing significance.